The Rate of Venous Thromboembolism Before and After Spine Surgery as Determined with Indirect Multidetector CT. Issue 3 (25th September 2018) - Inoue, Hirokazu; Watanabe, Hideaki; Okami, Hitoshi; Kimura, Atsushi; Takeshita, Katsushi
Abstract : Background: This prospective cohort study investigated the rate of venous thromboembolism (VTE) before and after spine surgery as determined with use of indirect multidetector computed tomography (MDCT). Methods: We performed a prospective study of 105 patients (36 women and 69 men ranging in age from 38 to 88 years) undergoing spine surgery at 2 institutions. Indirect MDCT was performed before and 3 days after surgery. Patients with a history of dialysis or drug allergy to contrast medium were excluded. Results: No patient had symptomatic VTE preoperatively or postoperatively. The preoperative and postoperative rates of asymptomatic VTE were 4.8% and 13.0%, respectively; the rates of asymptomatic pulmonary embolism were 2.9% and 8.0%, respectively; and the rates of asymptomatic deep venous thrombosis were 3.8% and 6.0%, respectively. Age, sex, height, weight, body mass index, operative time, volume of intraoperative blood loss, and specific comorbidities (diabetes, hypertension, cardiac disease, previous VTE, and previous anticoagulation treatment) were not found to be risk factors. Conclusions: Our findings demonstrated a low rate of preoperative VTE but a high rate of postoperative VTE in association with spine surgery. Surgeons need to be aware of the risk of VTE in patients undergoing spine surgery. MDCT is an effective and convenient technology for the early detection of VTE in such patients. Level of Evidence: PrognosticLevel I . See Instructions for Authors for a complete description of levels of evidence.